Prophetic Churches for the Metaverse: Communities That Sing the Melody of Hope - Angga Avila (Indonesian Journal of Theology, 2022)
With a number of churches racing towards the metaverse, this paper offers a preliminary response to the phenomenon of the meta-church from the context of Indonesian churches. Churches that adopt and participate in the metaverse ought to do so not simply to be another institution that holds worship or preaches there. Churches that enter the metaverse follow strategies that are driven by followers, likes, and viewers (Joas Adiprasetya) as digital equivalents for measuring attendance, building, and cash (Chloe Lynch) without a proper understanding of the nature of the metaverse and a lack of contextual awareness may unconsciously endorse and even underwrite a system that fosters injustice and inequality. To kindle such an awareness, in this article I wish to consider Belle, a 2021 Japanese animated movie that depicts a metaverse, which features Sponsors who capitalize on its resources and thereby abuse the metaverse by perpetuating deep inequities. The film illuminates the potential condition of a metaverse that promises unlimited possibility and purports to be impartial to everyone, insofar as it connects people and removes for many the barriers of time and distance. While I argue that Indonesian churches must learn from the prophetic character of Bitcoin, they must also stay vigilant against the inherent inequities brought to bear with the advent of the NFT (non-fungible token). Leveraging Joshua Nunzianto’s interpretation of an Augustinian economy of sacrifice, I re-evaluate the very concept of a metaversal economy based on notions of scarcity and proprietary ownership. Then, with reference to Walter Brueggemann’s Prophetic Imagination and Jürgen Moltmann’s The Spirit of Hope, I construct an ecclesiology of prophetic communities that sing the melody of hope.